Genetic Polymorphism of NQO1 Gene is Associated with Susceptibility of Ischemic Stroke in Chinese Han Nationality - Yan, Limin; Xu, Dedong; Xiao, Ying; Dai, Mingming; Wang, Ting; Zhuang, Xinhong; Wu, Kunliang (Neuropsychiatric disease and treatment, 2022)
Purpose: NAD(P)H: Quinone Oxidoreductase 1 gene (NQO1) polymorphism is associated with the risk of cardiovascular disease. This study was designed to investigate the relationship between NQO1 gene polymorphism and ischemic stroke susceptibility in Chinese Han nationality. Patients and Methods: One hundred and forty-one patients diagnosed with ischemic stroke and 139 matched control groups were recruited in this study. The polymorphism distribution of rsl800566 locus and rs10517 locus of NQO1 gene was genotyped via TaqMan assay, and the concentration of Oxidized low-density lipoprotein (ox-LDL) in the blood of the subjects was detected by enzyme linked immunosorbent assay (ELISA). The relationship between the polymorphism distribution and the susceptibility to ischemic stroke was evaluated. Results: The frequency distribution of the three genotypes of NQO1 rs1800566 between the case group and the control group was statistically significant, and cases carrying CT and TT genotype were less likely to suffer from ischemic stroke. Compared with individuals carrying T allele, C allele carriers have higher risk of ischemic stroke. However, there was no significant difference in frequency distribution among the three genotypes of NQO1 rs10517 between controls and patients. Conclusion: The NQO1 rs1800566 C allele may be a novel marker associated with ischemic stroke susceptibility in Chinese Han population. Polymorphism of rsl800566 locus in NQO1 gene may be protective against ischemic stroke risk.